Morphological and Molecular Characterization of Human Gingival Tissue Overlying Multiple Oral Exostoses - Luca Francetti; Claudia Dellavia; Stefano Corbella; Nicolò Cavalli; Claudia Moscheni; Elena Canciani; Nicoletta Gagliano (Case Reports in Dentistry)
Gingival and osseous augmentations are reported as hypertrophic or hyperplastic reactions to different factors including chronic traumatisms and surgeries such as free gingival graft (FGG) that induce an abnormal growth of both hard and soft tissues in genetically predisposed subjects. Since an imbalance in collagen turnover plays a key role in the development of gingival overgrowth leading to an accumulation of collagen in gingival connective tissue, in this study we described the histological and molecular features of three oral overgrowths obtained from a 34-year-old woman previously operated for FGG in order to evaluate a possible relationship between exostoses and overgrown tissue. Healthy and overgrown gingiva were analyzed by histological methods, and the expression of genes and proteins involved in collagen synthesis, maturation, and degradation was assessed in cultured fibroblasts obtained from gingival fragments at the molecular level. Our results show that general morphology and collagen content were similar in healthy and overgrown gingivae. However, fibroblasts obtained from the overgrown gingiva revealed an anabolic phenotype characterized by an increased collagen turnover and maturation. These findings indicate that an exostosis could act as a mechanical stimulus stretching the overlying connective tissue and triggering an anabolic phenotype of gingival fibroblasts and suggest to use minimally invasive surgical techniques to avoid traumatizing the periosteal tissues for the eradication of the exostosis with minimal relapses.